2015
DOI: 10.1002/cssc.201402945
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ultrathin Films of Hematite for Photoelectrochemical Water Splitting via H2 Treatment

Abstract: Thermal treatment of ultrathin films of hematite (α-Fe2 O3 ) under an atmosphere of 5 % H2 in Ar is presented as a means of activating α-Fe2 O3 towards the photoelectrochemical splitting of water. Spin-coated films annealed in air exhibited no photoactivity, whereas films treated in hydrogen exhibited a photocurrent response. X-ray photoelectron spectroscopy and UV/Vis absorption spectroscopy results showed that the H2 -treated films contain oxygen vacancies, which suggests improved charge transport. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 81 publications
(167 reference statements)
6
62
0
Order By: Relevance
“…Only a small fraction of the photogenerated holes are being transferred to the cocatalyst, likely due to the higher rate of recombination of electron−hole pairs in the hematite film close to the surface. 22,24,25 This is consistent with the TPC results described later on, which indicate there is no difference in the amount of charge available at the surface for the air-treated films before and after treatment with the cocatalyst. The rate of recombination within the hematite structure is therefore the limiting factor in these functionalized films.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Only a small fraction of the photogenerated holes are being transferred to the cocatalyst, likely due to the higher rate of recombination of electron−hole pairs in the hematite film close to the surface. 22,24,25 This is consistent with the TPC results described later on, which indicate there is no difference in the amount of charge available at the surface for the air-treated films before and after treatment with the cocatalyst. The rate of recombination within the hematite structure is therefore the limiting factor in these functionalized films.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…The hydrogen treatment is therefore key to increasing the donor density within the film as a result of the creation of oxygen vacancies. 24,29,30 These vacancies create Fe 2+ donor states that help to push the Fermi level of n-type α-Fe 2 O 3-x toward the conduction band, resulting in a more negative flat-band potential and a greater degree of band bending at lower applied potentials. 25 This result is fully consistent with the TPC results above and the presence of a The Journal of Physical Chemistry C Article photocurrent following hydrogen treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Fe oxidation state of the sample surfaces was further examined by XPS, which provides a depth analysis of a few nanometers. 33 Figure 3 summarizes the XPS results for the asprepared, PM and PH samples. The Fe 2p spectrum of the asprepared sample (Figure 3 (b)) reveals a typical Fe 2 O 3 spectrum having the binding energies of 710.2 eV for Fe 2p 3/2 and 723.6 eV for Fe 2p 1/2 , the shakeup satellite located at 718 eV, and the characteristic satellite peaks for the α-Fe 2 O 3 or γ-Fe 2 O 3 phases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8 Ozin et al investigated hightemperature treatment of ultrathin film of hematite under an atmosphere of H 2 and Ar and suggested that the generated oxygen vacancies upon high temperature treatment are responsible for the activation of the photoanode by improving the electron collection. 33 Finally, thermal annealing under oxygen-deficient atmosphere of hematite was reported as an efficient means to control oxygen vacancy density, which was used to increase the photocurrent of hematite photoanodes. 34,35 Herein, we combine a low-temperature fabrication technique of ultrathin hematite nanoflakes with a plasma post-treatment to control the density of oxygen vacancies and investigate the effect of oxygen vacancies on photocatalysis with the aim of realizing high photoactivity for nanostructured hematite photoanodes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[http://dx.doi.org/10.1063/1.4972223] α-Fe 2 O 3 , the most stable phase of iron oxides, has been applied in photoelectric devices, 1 gas sensors, 2 magnetic materials, 3 water treatment, 4 and lithium-ion batteries (LIBs), 5 according to their advantages of simple production, environmental friendliness, and chemical stability. Shape controlled synthesis and self-assembly of α-Fe 2 O 3 nanocrystals are major approaches to manipulate their functionalities.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%